(untitled) - Schiek, Burkhard (Hoboken, N.J., 2006)
This book examines noise phenomena in linear and nonlinear high-frequency circuits from both qualitative and quantitative perspectives. The authors explore important noise mechanisms using equivalent sources and analytical and numerical methods. Readers learn how to manage electrical noise to improve the sensitivity and resolution of communication, navigation, measurement, and other electronic systems. Noise in High-Frequency Circuits and Oscillators has its origins in a university course taught by the authors. As a result, it is thoroughly classroom-tested and carefully structured to facilitate learning. Readers are given a solid foundation in the basics that allows them to proceed to more advanced and sophisticated themes such as computer-aided noise simulation of high-frequency circuits.
Keywords: Electronic circuits,Electronic circuit design,Electromagnetic noise; Noise